(untitled) (International Journal of Engineering and Computer Science, 2017)
An increasing rate of multi-media increases the verity of multi-media data such as image video voice and text. The size of these data need more space for storage and more bandwidth for transmission. For the flexibility of storage and transmission used lossless image compression technique. The lossless image compression is very efficient but faced the problem of compression ratio. In series of image compression fractal transform function are used. Fractal transform based by virtue of symmetry. The symmetry nature of fractal wavelet transform provides block level image compression technique. But the process of computational is poor then the performances of fractal transform function are decease. In this paper presents review of lossless image compression based on fractal transform function and used block co-efficient technique